2012
DOI: 10.1089/ees.2011.0297
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations and Profiles of Polychlorinated Dibenzo-p-Dioxins and Dibenzofurans in Air and Soil Samples in the Proximity of a Municipal Solid Waste Incinerator Plant

Abstract: This study investigated the influence of polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs) in the waste gas from an incinerator on the surrounding environment. A series of air and soil samples were collected at distances from 1.35 to 4.72 km from a typical municipal solid waste incineration plant along the prevailing north wind direction. Concentrations of PCDD/Fs in the ambient air samples ranged from 0.23 to 1.66 pg I-toxic equivalent (TEQ)/m 3 , with an average of 0.82 pg I-TEQ/m 3 ; while conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…It can be seen that the PCDD/F concentrations in ambient air near the SeAl plants in our study were similar to those found near a crematory by Wang et al (2003), near a SeAl plant by Chen et al (2004), and near MSWIs (Oh et al, 2002;Xu et al, 2009;Liu et al, 2012b). However, the PCDD/F concentrations in ambient air near the SeCu smelters in our study were higher than those of industrial thermal processes listed in Table 3, so it is essential that intensive studies are performed to investigate the potential impacts of SeCu plants on their surrounding environments.…”
Section: Comparison Of Atmospheric Up-pops Concentrations With Some Isupporting
confidence: 83%
See 3 more Smart Citations
“…It can be seen that the PCDD/F concentrations in ambient air near the SeAl plants in our study were similar to those found near a crematory by Wang et al (2003), near a SeAl plant by Chen et al (2004), and near MSWIs (Oh et al, 2002;Xu et al, 2009;Liu et al, 2012b). However, the PCDD/F concentrations in ambient air near the SeCu smelters in our study were higher than those of industrial thermal processes listed in Table 3, so it is essential that intensive studies are performed to investigate the potential impacts of SeCu plants on their surrounding environments.…”
Section: Comparison Of Atmospheric Up-pops Concentrations With Some Isupporting
confidence: 83%
“…The PCDD/F concentrations in ambient air around SeAl plant and plants performing other industrial thermal processes have been studied previously, and the results are summarized in Table 3 (Oh et al, 2002;Wang et al, 2003;Chen et al, 2004;Shih et al, 2006;Xu et al, 2009;Liu et al, 2012b). It can be seen that the PCDD/F concentrations in ambient air near the SeAl plants in our study were similar to those found near a crematory by Wang et al (2003), near a SeAl plant by Chen et al (2004), and near MSWIs (Oh et al, 2002;Xu et al, 2009;Liu et al, 2012b).…”
Section: Comparison Of Atmospheric Up-pops Concentrations With Some Isupporting
confidence: 73%
See 2 more Smart Citations
“…And the D/F ratios for stack gas samples were in the range of 0.085-0.31 (mean 0.20), which were in accordance with previous studies. Liu et al (2012) found that the D/F ratios in the stack gas samples usually less than 1, which indicated the emission characteristics of PCDD/Fs during thermal processes. However, the D/F ratios in the soil samples were different from the air samples and increased in the soil environment (Liu et al 2012).…”
Section: Pcdd/f Concentrations At Different Distances From the Stacksmentioning
confidence: 96%